2021
DOI: 10.3390/ijms22157808
|View full text |Cite
|
Sign up to set email alerts
|

Gasotransmitters for the Therapeutic Prevention of Hypertension and Kidney Disease

Abstract: Nitric oxide (NO), carbon monoxide (CO), and hydrogen sulfide (H2S), three major gasotransmitters, are involved in pleiotropic biofunctions. Research on their roles in hypertension and kidney disease has greatly expanded recently. The developing kidney can be programmed by various adverse in utero conditions by so-called renal programming, giving rise to hypertension and kidney disease in adulthood. Accordingly, early gasotransmitter-based interventions may have therapeutic potential to revoke programming proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 131 publications
(262 reference statements)
1
13
0
Order By: Relevance
“…However, the extent to which the organ-specific expression of NO synthase enzymes was affected by STS awaits further evaluation. Notably, previous studies have revealed cross-talk mechanisms between H 2 S, NO, and carbon monoxide (CO) against hypertension [ 4 , 6 ]. H 2 S can modify cysteine residues on key signaling molecules such as nuclear factor erythroid 2-related factor 2 (NRF2) and nuclear factor κB (NFκB), thereby promoting antioxidant and anti-inflammatory effects [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the extent to which the organ-specific expression of NO synthase enzymes was affected by STS awaits further evaluation. Notably, previous studies have revealed cross-talk mechanisms between H 2 S, NO, and carbon monoxide (CO) against hypertension [ 4 , 6 ]. H 2 S can modify cysteine residues on key signaling molecules such as nuclear factor erythroid 2-related factor 2 (NRF2) and nuclear factor κB (NFκB), thereby promoting antioxidant and anti-inflammatory effects [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that a reduction in H 2 S synthesis may be a key mechanism underlying hypertension and kidney disease [ 1 , 2 , 4 ]. In the kidneys, a mismatch of vasodilators, such as H 2 S and nitric oxide (NO), and vasoconstrictors, such as angiotensin II (Ang II), in favor of the latter, may ultimately lead to hypertension [ 5 , 6 ]. Conversely, H 2 S-based modalities have been developed for therapeutic protection against hypertension and kidney disease [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a single episode of severe AKI superimposed on patients with pre-existing CKD can cause further renal deterioration to end-stage kidney disease (ESKD) rapidly at a non-linear pace ( Figure 1 B). The risk factors associated with the AKI-related acceleration of renal progression were identified previously, and include older age, delayed renal function recovery from AKI, severe AKI episodes, the presence of proteinuria, and comorbidities such as DM, hypertension, and heart failure [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , ...…”
Section: Avoidance Of Acute Kidney Injury (Aki) In Patients With Ckdmentioning
confidence: 99%
“…Besides lifestyle modifications, including salt restriction, smoking cessation, weight loss, and adequate exercise, pharmacotherapy can be beneficial with the use of renoprotective agents, including RAAS blockades and carvedilol [ 80 , 81 , 82 ]. Mineralocorticoid receptor antagonists (MRAs), such as spironolactone, are able to reduce proteinuria and BP, but are limited in the treatment of CKD due to their association with GFR decline and hyperkalemia [ 83 , 84 , 85 ].…”
Section: Hypertension-related Ckdmentioning
confidence: 99%
“…Likewise, RAS-based interventions have also shown promising results in protecting against renal programming and related diseases, such as renin inhibitor, ACE inhibitor, ACE-2 (ACE2) activator, and ARBs [111]. Furthermore, reprogramming interventions targeting the hydrogen sulfide (H 2 S) pathway [146] and nutrient-sensing signals [147] have also shown benefits with regard to kidney disease of developmental origin. Although significant advances have been made from animal research, the need for meaningful clinical translation remains a research priority.…”
Section: Prevention Actionsmentioning
confidence: 99%